THE EFFECT OF SELF-EFFICACY, FAMILY ENVIRONMENT AND ENTREPRENEURSHIP EDUCATION ON ENTREPRENEURIAL INTENTIONS: (Study on Students of the Islamic University of Malang) - Febyanti, Anggi Try; Saroh, Siti; Hardati, Ratna Nikin (Transpublika Publisher, 2022)
This research aims to determine the effect of self-efficacy, family environment and entrepreneurship education on entrepreneurial intentions. This type of research is quantitative. Methods of data collection using the distribution of questionnaires. This research carried out at Islamic University of Malang while objects of this research are students of the Islamic University of Malang. The populations were undergraduate students at the Islamic University of Malang with a total population of 13.898 students, and the number of samples was determined by Slovin formula which obtain 100 respondents then processed using the SPSS V.28 application for windows. Based on the results of the partial test, it shows that the self-efficacy variable has a positive and significant effect on Entrepreneurial Intentions, the Family Environment variable has a positive and significant impact on Entrepreneurial Intentions and Entrepreneurship Education has a positive and significant impact on Entrepreneurial Intentions. Based on the Simultaneous test, the variables of Self-Efficacy, Family Environment and Entrepreneurship Education have a positive and significant effect on Entrepreneurial Intentions.